An optimized whole blood assay measuring expression and activity of NLRP3, NLRC4 and AIM2 inflammasomes - Grinstein, Lev (Clinical immunology (Orlando, Fla.), 2018)
Copyright © 2017 Elsevier Inc. All rights reserved.